2000
DOI: 10.1159/000012411
|View full text |Cite
|
Sign up to set email alerts
|

Antonovsky’s Sense of Coherence: Trait or State?

Abstract: Background: The aim of this study was first to analyze the stability of Antonovsky’s Sense of Coherence (SOC) as a measure of a person’s world view over time; secondly, to investigate its relationship with depression and anxiety. Methods: Data from two longitudinal studies were used: a study of severely injured accident victims (n = 96), and a study of patients suffering from rheumatoid arthritis (RA, n = 60). The 13 items short version of the SOC scale and measures of depression and anxiety (Symptom Checklist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
3
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(188 citation statements)
references
References 25 publications
12
163
3
10
Order By: Relevance
“…to -0.75 (2,22) . Another study found correlations that ranged from moderate to strong magnitude between sense of coherence and the measures of anxiety and depression (r= -0.28 and r= -0.73, p<0.01) (12) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…to -0.75 (2,22) . Another study found correlations that ranged from moderate to strong magnitude between sense of coherence and the measures of anxiety and depression (r= -0.28 and r= -0.73, p<0.01) (12) .…”
Section: Discussionmentioning
confidence: 97%
“…Presence of depression and anxiety has been strongly associated with a low level of sense of coherence (1)(2)12,22) . to -0.75 (2,22) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sense of coherence can change, even if it is to be understood more as something that develops into a personality trait. This may come about as a result of external influences, for example when a person's life undergoes radical changes lasting for a long period of time (Surtees et al 2006) or is impacted by traumatic events (Schnyder et al 1999(Schnyder et al , 2000.…”
Section: Theoretical Perspectivementioning
confidence: 99%